Curled cation structures accelerate the dynamics of ionic liquids. Issue 37 (15th September 2021) - Rauber, Daniel; Philippi, Frederik; Kuttich, Björn; Becker, Julian; Kraus, Tobias; Hunt, Patricia; Welton, Tom; Hempelmann, Rolf; Kay, Christopher W. M.
Abstract : The curled cation structures of ionic liquids with three ether groups show significantly accelerated dynamics compared to the structural analogues with alkyl side chains. Abstract : Ionic liquids are modern liquid materials with potential and actual implementation in many advanced technologies. They combine many favourable and modifiable properties but have a major inherent drawback compared to molecular liquids – slower dynamics. In previous studies we found that the dynamics of ionic liquids are significantly accelerated by the introduction of multiple ether side chains into the cations. However, the origin of the improved transport properties, whether as a result of the altered cation conformation or due to the absence of nanostructuring within the liquid as a result of the higher polarity of the ether chains, remained to be clarified. Therefore, we prepared two novel sets of methylammonium based ionic liquids; one set with three ether substituents and another set with three butyl side chains, in order to compare their dynamic properties and liquid structures. Using a range of anions, we show that the dynamics of the ether-substituted cations are systematically and distinctly accelerated. Liquefaction temperatures are lowered and fragilities increased, while at the same time cation–anion distances are slightly larger for the alkylated samples. Furthermore, pronounced liquid nanostructures were not observed. Molecular dynamics simulations demonstrate that the origin of the altered properties of the ether substituted ionic liquids is primarily due to a curled ether chain conformation, in contrast to the alkylated cations where the alkyl chains retain a linear conformation. Thus, the observed structure–property relations can be explained by changes in the geometric shape of the cations, rather than by the absence of a liquid nanostructure. Application of quantum chemical calculations to a simplified model system revealed that intramolecular hydrogen-bonding is responsible for approximately half of the stabilisation of the curled ether-cations, whereas the other half stems from non-specific long-range interactions. These findings give more detailed insights into the structure–property relations of ionic liquids and will guide the development of ionic liquids that do not suffer from slow dynamics.